Analysis of Police Efforts in Combating Online Gambling Crimes - Ach Badawi; Delviani Damanik (ISNU Sumatera Utara, 2025)
Online gambling is a form of gambling conducted over the internet, offering a variety of games such as casino games, slots, poker, and sports betting. With the increasing popularity of the internet and technological advancements, online gambling has become increasingly popular among the public, including teenagers. While offering convenience and entertainment, this phenomenon also carries serious risks, such as addiction, financial loss, and legal issues. Different countries implement different regulations regarding online gambling, ranging from prohibitions to strict regulations. Therefore, it is crucial to raise awareness and education about the risks associated with online gambling and the importance of playing responsibly. This study aims to analyze two things: first, the efforts made by the police in enforcing the law against perpetrators of online gambling crimes in the Percut Sei Tuan Police Sector; second, the obstacles that hinder law enforcement against perpetrators of online gambling crimes in Deli Serdang Regency. This study uses an empirical legal approach with a descriptive nature, and involves the collection of primary and secondary data. Data collection techniques were carried out through observation, interviews, and document studies. The sampling used a non-probability sampling method in the form of purposive sampling, and data analysis used a qualitative approach. The research results show that police efforts to address online gambling crimes in the Percut Sei Tuan Police Station area are carried out through penal law enforcement methods. However, obstacles encountered include difficulty in obtaining suspects' addresses and the perpetrators' high level of information technology proficiency. To increase the effectiveness of law enforcement, the police, as a law enforcement agency, are committed to improving performance, maintaining public security and order, and strengthening relationships with various parties to better carry out their duties.